Analisis Harga Air Pada Air Permukaan Untuk Usahatani Padi Sawah di Subak Bengkel, Kecamatan Kediri, Kabupaten Tabanan - Paramarta, Pande Made Ari Ananta; Widhianthini, Widhianthini; Djelantik, AA Wulandira Sawitri (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2020)
Bengkel Subak is the widest subak in Kediri District, Tabanan Regency. Subak Bengkel has a total area of 329 hectares, which is divided into 19 Tempek, which is some kind of grouping. Bengkel Subak is located on two villages, Bengkel Village and Pangkung Tibah Village. The water acquisition is also agreed based on the water debit in each place. This study aims to determine the price of water used by farmers in Subak Bengkel paddy farming, also to know the influence of production and constraints factors experienced in rice farming. The results calculation with the use of value of marginal product (VMP) approach showed that the price of water for irrigated paddy in Subak Bengkel was Rp 413,593.85 / ha / year, around 206,796.92 / ha / planting season or around Rp 206.79 / m3, where the most influential factor is seedlings with an elasticity coefficient of 0.861 affecting production of 8.61 percent. The most common obstacle experienced by Subak Bengkel farmers is the pest in the form of crabs that damage the rice field dike. In the future, Bengkel Subak will include water discharge as an production input in rice farming for appreciation of water resources.